Generation of a Broadly Useful Model for COVID-19 Pathogenesis, Vaccination, and Treatment - Sun, Jing; Zhuang, Zhen; Zheng, Jian; Li, Kun; Wong, Roy Lok-Yin; Liu, Donglan; Huang, Jicheng; He, Jiangping; Zhu, Airu; Zhao, Jingxian; Li, Xiaobo; Xi, Yin; et al. (Cell, 2020)
COVID-19, caused by SARS-CoV-2, is a virulent pneumonia, with >4,000,000 confirmed cases worldwide and >290,000 deaths as of May 15, 2020. It is critical that vaccines and therapeutics be developed very rapidly. Mice, the ideal animal for assessing such interventions, are resistant to SARS-CoV-2. Here, we overcome this difficulty by exogenous delivery of human ACE2 with a replication-deficient adenovirus (Ad5-hACE2). Ad5-hACE2-sensitized mice developed pneumonia characterized by weight loss, severe pulmonary pathology, and high-titer virus replication in lungs. Type I interferon, T cells, and, most importantly, signal transducer and activator of transcription 1 (STAT1) are critical for virus clearance and disease resolution in these mice. Ad5-hACE2-transduced mice enabled rapid assessments of a vaccine candidate, of human convalescent plasma, and of two antiviral therapies (poly I:C and remdesivir). In summary, we describe a murine model of broad and immediate utility to investigate COVID-19 pathogenesis and to evaluate new therapies and vaccines. [Display omitted] •Mice are sensitized for SARS-CoV-2 infection by Ad5-hACE2 transduction•Genetically deficient strains can be directly assessed without additional breeding•Mice useful for determining host factors necessary for optimal virus clearance•Useful for assessing efficacy of vaccines and therapies such as convalescent plasma An adenoviral transduction-based mouse model that can be infected with SARS-CoV-2 provides a tool to understand host factors involved in viral infection and clearance as well as potential therapeutic modalities.